2016
DOI: 10.13031/trans.59.11158
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Apps for Irrigation Scheduling

Abstract: SmartIrrigation apps were developed to provide real-time irrigation schedules for selected crops (i.e., avocado, citrus, cotton, peanut, strawberry, and vegetables). Irrigation schedules in the smartphone apps are based on evapotranspiration (ET) or a water balance methodology using real-time weather data from the Florida Automated Weather Network and the Georgia Environmental Monitoring Network. The FAO Penman-Monteith method is used for calculating reference ET, and crop coefficients (K c) are applied based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 19 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Multiple causes explain why irrigators do not implement new irrigation technologies (Abdullah and Samah, 2013;Mottaleb, 2018). Irrigation scheduling decision-support applications such as smartphone apps, web-based platforms, and desktop programs bridge the existing timing and water-related knowledge gap in irrigation methods (Migliaccio et al, 2016). Thousands of valuable irrigation-related data can currently be retrieved in a publicly available and near-real-time manner through online applications.…”
Section: Applications Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple causes explain why irrigators do not implement new irrigation technologies (Abdullah and Samah, 2013;Mottaleb, 2018). Irrigation scheduling decision-support applications such as smartphone apps, web-based platforms, and desktop programs bridge the existing timing and water-related knowledge gap in irrigation methods (Migliaccio et al, 2016). Thousands of valuable irrigation-related data can currently be retrieved in a publicly available and near-real-time manner through online applications.…”
Section: Applications Comparisonmentioning
confidence: 99%
“…The IS smartphone app used by the avocado growers detailed above goes by the name Smartirrigation Avocado and can be found in the Google Play and Apple App Stores (Migliaccio et al, 2016). This app requires input parameters such as the irrigation system, the crop, the soil type, and IS characteristics to output the accumulated precipitation for the seven previous days, the applied irrigation events timing, and the reached moisture depth.…”
Section: Appsmentioning
confidence: 99%
“…Although modern sciencebased irrigation scheduling has existed for approximately 60 years, with one of the first reports by Van Bavel (1956), the long-term and consistent adoption of appropriate irrigation scheduling has been dismal (Shearer and Vomacil, 1981;Lamm and Rogers, 2015). To facilitate better adoption rates and improved irrigation scheduling, Migliaccio et al (2016) developed a software application (i.e., smartphone and tablet app) to provide real-time irrigation schedules for various crops (avocado, citrus, cotton, peanut, strawberry, urban turf, cabbage, squash, tomato, and watermelon) in the southeastern U.S. The application can use real-time weather data from both the Florida Automated Weather Network and the Georgia Environmental Monitoring Network to calculate crop ET using a water balance method for scheduling irrigation.…”
Section: Irrigation Scheduling and Water Managementmentioning
confidence: 99%
“…In some cases, remote sensing observations are also integrated (Thysen and Detlefsen, 2006;D'Urso et al, 2010;Melton et al, 2012;Montgomery et al, 2015;Vuolo et al, 2015). Services are usually provided as online applications (Montoro et al, 2011;Palmer, 2011;Kaloxylos et al, 2014;Giannerini and Genovesi, 2015) or by a specific app available for end-users (Li et al, 2013;Bartlett et al, 2015;Migliaccio, 2016). Despite some difficulties identified for the integration of the service in some contexts (Walker, 2002;Bjornlund et al, 2009;Lorite et al, 2012;Tapsuwan et al, 2015;Giannakis et al, 2016), the systems were shown to be a relevant support for the improvement and assessment of the agricultural water management.…”
Section: Introductionmentioning
confidence: 99%